Механизмы, клиническая значимость и взаимоотношение тканевого фиброза и фибрилляции предсердий = Mechanisms, clinical significance and relationship of tissue fibrosis and atrial fibrillation = Механізми, клінічна значущість та взаємовідношення тканинного фіброзу і фібриляції передсердь - Gozhenko, A. I.; Levchenko, E. M.; Goriachyi, V. V.; Goriachyi, A. V. (Journal of Education, Health and Sport, 2017)
Atrial fibrillation (AF) is the most common heart rhythm disorder in clinical practice. Today proved that traditional pharmacologic therapies are effective in patients with paroxysmal atrial fibrillation with no structural disorders of the myocardium. Data from clinical and experimental studies have shown the important role of the structural remodeling in the formation of the substrate of atrial fibrillation, producing fibrosis that alters the composition and function of the atrial tissue. The exact mechanism underlying atrial fibrosis is not fully elucidated, but recent experimental and clinical studies have provided important data. It has been shown that in the process of formation and propagation of fibrosis involved number of different signaling systems, including angiotensin-2 and related mediators. This article provides an overview of the current understanding of the formation of atrial fibrillation substrate by fibrosis remodeling. Sum-date data on the mechanisms underlying the fibrosis and progression as well as brightly lit modern therapeutic approaches aimed at reducing structural remodeling to prevent AF.